Pengaruh Model Pembelajaran Problem Based Learning Terhadap Elemen Menulis Negosiasi Fase E SMA Negeri 9 Mandau - Hamidah Faradilla Suciani Faradilla Suciani; Suci Dwinitia; Upit Yulianti Dn (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
This research aims to describe the effect of the Problem Based Learning Method on Learning to Write Negotiation Texts for Class X Students of SMA Negeri 9 Mandau. This type of research is quantitative research with experimental methods. The population of this study were 306 students of class X SMA Negeri 9 Mandau who were enrolled in the 2023/2024 academic year. The sample of this research is class X.2 students. The data in this study are the performance scores of the ability to write negotiating texts of class X students of SMA Negeri 9 Mandau before and after using the Problem Based Learning Method. The results of this study are based on data analysis, namely that there is a significant effect of using the Problem Based Learning method on the ability to write negotiating texts for class X students of SMA Negeri 9 Mandau because tcount>ttable on degrees of freedom (dk)=n1-1 and (?)=0.05 significant level of 95%.